ANALISIS PENERAPAN ISO 3100 DALAM MANAJEMEN RISIKO DI PT.XYZ - Nur Habibah Angkat; Arsyadona Arsyadona (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the application of ISO 31000 in risk management at PT. XYZ, which faces challenges in identifying and managing operational risks. The purpose of this research is to examine the effectiveness of implementing ISO 31000 standards in reducing risks and improving the company's operational efficiency. A case study method with a qualitative approach was used, involving in-depth interviews and document analysis related to risk management. The results indicate that the implementation of ISO 31000 assists PT. XYZ in building a systematic framework for risk identification, evaluation, and mitigation, thereby reducing the frequency and impact of operational risks. This research is expected to serve as a reference for other companies implementing ISO 31000 standards.